2014
DOI: 10.5588/ijtld.13.0268
|View full text |Cite
|
Sign up to set email alerts
|

Serum concentrations of cycloserine and outcome of multidrug-resistant tuberculosis in Northern Taiwan

Abstract: Lower than recommended serum CS concentrations and delayed absorption were common. It is essential to develop practical TDM to maintain proper serum drug concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 0 publications
0
14
3
Order By: Relevance
“…A possible explanation for this finding is that treatment of MDR-TB includes multiple drugs, and an observational study without strict placebo controls hardly assesses the efficacy of a single agent. Furthermore, a recent study has shown that more than half of patients with the recommended dosage of 10 mg/kg of cycloserine prescription had peak serum concentrations lower than the minimum inhibitory concentrations of the strains isolated from the corresponding patients, suggesting the need for adjusting each patient’s dosages depending on the clinical pharmacokinetic and pharmacodynamic assessments 24,25…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this finding is that treatment of MDR-TB includes multiple drugs, and an observational study without strict placebo controls hardly assesses the efficacy of a single agent. Furthermore, a recent study has shown that more than half of patients with the recommended dosage of 10 mg/kg of cycloserine prescription had peak serum concentrations lower than the minimum inhibitory concentrations of the strains isolated from the corresponding patients, suggesting the need for adjusting each patient’s dosages depending on the clinical pharmacokinetic and pharmacodynamic assessments 24,25…”
Section: Discussionmentioning
confidence: 99%
“…Figure 1 shows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) diagram summarizing literature search findings for d-cycloserine, which shows that hitherto there have been no PK/PD studies performed in preclinical models. There were 9 pharmacokinetic studies; 2 were duplicates, leading to 7 studies shown in Supplementary Table 1 [26,28,38,[43][44][45][46]. Doses of cycloserine used in the pharmacokinetic studies ranged from 250 mg twice a day to 500 mg twice a day.…”
Section: Monte Carlo Experiments For Dose Selectionmentioning
confidence: 99%
“…Cycloserine was predominately employed at a low dose (250 mg daily) and TDM used to mitigate toxicity. This approach contrasts to a more commonly reported twice daily dosing with targets of 15 mg/kg or 750 mg total daily dose, such as recent report from Taiwan which confirmed a total daily dose correlation with peak concentration, as well as an event of psychosis in a patient with concentrations >35 µg/mL 21 . The low-dose approach did not appear to compromise treatment efficacy in our setting and minimized toxicity.…”
Section: Discussionmentioning
confidence: 74%